2012
DOI: 10.1039/c2jm16470a
|View full text |Cite
|
Sign up to set email alerts
|

Impact of mechanical bending on the electrochemical performance of bendable lithium batteries with paper-like free-standing V2O5–polypyrrole cathodes

Abstract: Highly flexible, paper-like, free-standing V 2 O 5 and V 2 O 5 -polypyrrole (PPy) films were prepared via the vacuum filtration method. The films are soft, lightweight, and mechanically robust. The electrochemical performance of the free-standing pure V 2 O 5 electrode was improved by incorporating conducting polypyrrole. A bendable cell with a novel design was fabricated, consisting of a freestanding V 2 O 5 -PPy cathode film, gel electrolyte, and a lithium foil anode. The cell was tested under repeated bendi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 40 publications
0
30
0
Order By: Relevance
“…This type of anode is not suitable for flexible or bendable LIBs because it suffers from serious cracking and damage caused by the weak bonding between the metal substrate and the other materials during frequent bending. To avoid this drawback and lower the cost of LIBs, the development of free-standing anode materials is required [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…This type of anode is not suitable for flexible or bendable LIBs because it suffers from serious cracking and damage caused by the weak bonding between the metal substrate and the other materials during frequent bending. To avoid this drawback and lower the cost of LIBs, the development of free-standing anode materials is required [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…A free-standing PPy-LiFePO 4 film was prepared by coating the 0.06 M pyrrole and 0.05 M tetrabutylammonium hexafluorophosphate/propylene carbonate with LiFePO 4 powder onto a polished stainless steel plate, followed by the peeling off of the film after galvanostatic deposition for 1 h. The composite film exhibited a discharge capacity of 80 mAh/g, which is higher than that of PPy film (60 mAh/g) used as a comparison sample. Noerochim et al reported a paper-like free-standing V 2 O 5 -polypyrrole cathode [32]. In this case, they used an additional steel mesh as a current collector and the polypyrrole as active material.…”
Section: Conducting Polymersmentioning
confidence: 99%
“…Typical conductive polymers such as poly (3, 4-ethylenedioxythiophene) (PEDOT) [152] and polypyrrole (Ppy) [153] were widely applied as coating materials on V 2 O 5 nanostructures. The specific capacity, cycling stability, and high rate capacity can be effectively improved.…”
Section: Vanadium Oxide Nanocomposites In Libsmentioning
confidence: 99%